Advances in CO2 capture and separation materials: Emerging trends, challenges, and prospects for sustainable applications - Hailing Ma; Hongxin Fu; Yao Tong; Ahmad Umar; Yew Mun Hung; Xin Wang (Carbon Capture Science & Technology)
Carbon dioxide (CO2) remains a critical driver of climate change, necessitating the development of advanced carbon capture (CC) technologies to mitigate its atmospheric accumulation. This review provides a detailed evaluation of both conventional and emerging CC methods, highlighting the evolution from traditional physical/chemical adsorption and absorption techniques to innovative strategies based on cutting–edge materials science. In particular, the article examines the synthesis, functionalization, and performance of various porous adsorbents—including activated carbon, zeolite molecular sieves, metal–organic frameworks (MOFs), and covalent organic frameworks (COFs)—as well as hybrid composites that integrate the strengths of multiple materials. Advances in material design, such as pore modulation, surface functionalization, and the introduction of defect sites, have led to significant improvements in CO2 adsorption capacity, selectivity, and regeneration efficiency, while addressing challenges such as high energy consumption, moisture sensitivity, and production cost. Moreover, the integration of CC materials with catalytic processes for CO2 conversion into valuable chemicals is discussed as a promising route toward establishing a circular carbon economy. By outlining recent innovations and identifying key research directions—including the development of cost–effective synthesis methods and robust hybrid systems—this review aims to provide a comprehensive perspective on the state–of–the–art in CC materials and their potential role in achieving global climate mitigation goals.